The normative study of the legal force of electronic mediation in digital business dispute resolution - Hasjim, Andi Tri Utami; Poetry, Farahadayune Naharani (Priviet Social Sciences Journal, 2026)
The growth of Indonesia's digital economy, driven by startups and digital investments, has amplified business disputes. Traditional litigation is often inadequate, increasing the reliance on mediation. While current regulations (Law 30/1999, PERMA 1/2016) govern conventional mediation, the shift to electronic (online) mediation presents critical normative challenges in the digital business context. Despite the benefits of online mediation (efficiency, cost-effectiveness), before the enactment of PERMA No. 3 of 2022, specific provisions regarding its implementation, validity, and the binding nature of its outcomes were scarce. Major issues persist concerning the legal effects of electronic mediation agreements, particularly regarding electronic contracts, signature validity, and enforcement mechanisms in startup-investor disputes. Key uncertainties include the legal standing of the agreements, their equivalence to arbitration awards, and the precise procedure for their confirmation. This research conducts a normative study on the Legal Power of Electronic Mediation in Digital Business Dispute Resolution. By analyzing relevant regulations and the concept of electronic contracts, this study aims to clarify the legal status, certainty, confirmation mechanism (e.g., court ratification), and legal implications of violating an online mediation agreement within the Indonesian legal system.